Assessment of Ta'widh and Gharamah in Islamic financing contract and its' applicability potential for construction works contracts - Mohamad Hamdan, Noor Aishah; Ahmad Sarkawi, Azila; Abdullah Habib, Siti Nora Haryati; Othman, Ahmad Azam (e-International Publishing House Ltd, 2020)
Ta'widh and gharamah are the Shariah compliant late payment charges for Islamic financial contracts. Seven identified themes were used to qualitatively compare and contrast between the Guidelines on Late Payment Charges for Islamic Banking Institutions (2012) against the provisions of interest for late interim payment from four Malaysian construction works contracts. The findings revealed similarities and differences for identification of Shariah compliance. Recommendations were made for the harmonisation of ta'widh and gharamah in the construction works contracts while ensuring its practical and legal applicability. The outcome is beneficial for Islamic organisations and Muslims involved with the construction works.